High-Level Expression of Functionally Active Dengue-2 Non-Structural Antigen 1 Production in Escherichia coli. (8th September 2013) - Sankar, S. Gowri; Dhanajeyan, K. J.; Paramasivan, R.; Thenmozhi, V.; Tyagi, B. K.; Vennison, S. John
Abstract : Detection of nonstructural protein (NS1) is an important diagnostic marker during acute phase of dengue infection. Not only for diagnostic purpose, the protein had important role in vaccine design as well, as a candidate for studying virus assembly and maturation. Various researchers employed different expression systems and strategies for recombinant NS1 protein production. Attempts to express NS1 protein in prokaryotic and yeast expression system result in formation of insoluble protein which needs to undergo refolding to attain native structural and functional forms. Here, we report the production of soluble NS1 protein in E. coli by using appropriate vector and employing suitable culture conditions to maximize protein production. Proteins were purified using metal affinity chromatography. SDS-PAGE and western blot analysis reveal the native structure of NS1 protein. Solid phase ELISA using the recombinantly expressed antigen with positive and negative dengue samples showed that the expressed protein retains its antigenic and immunological properties. To our knowledge, this is the first report on the successful production of functionally active recombinant dengue-2 NS1 protein production without undergoing any in vitro posttranslational modification process.